(untitled) (Philological Studies, 2019)
The article raised the problem of studying the interaction between the Church Slavonic and Russian languages in the Russian linguistic and cultural space. The thesis of the article is that the medieval Church Slavonic-Russian diglossia is stored in the modern Russian literary language, and that the church-religious style of the Russian language forms a kind of transitional space between literary styles of the Russian language (lexical and syntactic base of which is based on genetically Church Slavonic language means) and the actual Church Slavonic (liturgical) language.